KnowledgeFlood: Sharing volunteers' experience |on flood disaster using storytelling - Kalid, K.S. (Institute of Electrical and Electronics Engineers Inc., 2016)
Floods is a common disaster that happens every year in Malaysia. Relief efforts involving government and non-government agencies are continuously dispatched to affected areas. Volunteers gain experience after participating in disaster relief efforts. Volunteer's experience are circulated but not captured. Volunteers are irreplaceable resources in disaster relief efforts because of their valuable experience. In knowledge management, experiences are an example of tacit knowledge. Tacit knowledge is regarded as one of the main challenges in knowledge management. One of the best ways in sharing tacit knowledge is using storytelling. As part of knowledge management, storytelling offers sharing of a more structured and absorbable form of tacit knowledge. This paper presents the use of storytelling as a medium to share tacit knowledge in the context of flood disaster relief missions among volunteers through a knowledge sharing platform called KnowledgeFlood. Â© 2016 IEEE.